2012
DOI: 10.1056/nejmp1208061
|View full text |Cite
|
Sign up to set email alerts
|

Brain Amyloid Imaging — FDA Approval of Florbetapir F18 Injection

Abstract: Brain health, or cognitive health, refers to skills such as remembering, learning new things, planning, concentrating, or making decisions. When cognitive health is impaired (referred to as cognitive impairment), a person has trouble with these skills that affect the things he or she can do in everyday life. People of all ages can experience cognitive impairment, which can range from mild to severe. A person with mild cognitive impairment may be aware of increased difficulty remembering, but it may not be obvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
106
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(109 citation statements)
references
References 2 publications
0
106
0
2
Order By: Relevance
“…For the detection of amyloid fibrils, great progress has been made to non-invasively image Aβ plaque deposition in the brain of Alzheimer's patients using PET, which has resulted in the approval of 18 F-Florbetapir by the US Food and Drug Administration (FDA). 116 It is likely that similar tracers may have the potential to visualize amyloid fibrils found in arterial plaques. Concurrently, alternate imaging strategy targeted at earlier oligomeric, pre-fibril species can be developed, in parallel with an increasing shift of focus in the field, where more evidence points to these intermediary assemblies as the toxic species.…”
Section: New Probe Developmentmentioning
confidence: 99%
“…For the detection of amyloid fibrils, great progress has been made to non-invasively image Aβ plaque deposition in the brain of Alzheimer's patients using PET, which has resulted in the approval of 18 F-Florbetapir by the US Food and Drug Administration (FDA). 116 It is likely that similar tracers may have the potential to visualize amyloid fibrils found in arterial plaques. Concurrently, alternate imaging strategy targeted at earlier oligomeric, pre-fibril species can be developed, in parallel with an increasing shift of focus in the field, where more evidence points to these intermediary assemblies as the toxic species.…”
Section: New Probe Developmentmentioning
confidence: 99%
“…152 Furthermore, in 2012, the U.S. Food and Drug Administration approved florbetapir ( 18 F) --a PET radiopharmaceutical agent that binds to amyloid aggregates --for clinical use in adults being evaluated for AD diagnosis. 153 Regarding CVRFs, preliminary amyloid imaging studies with PET have shown that engagement in physical exercise may be associated with decreased amyloid deposition in cognitively normal older adults 154 and that sedentary APOE e4 allele carriers exhibit greater amyloid deposition than physically active carriers. 122 Moreover, a study of late middle-aged to older adult subjects showed that systolic blood pressure correlated positively with 11 C-PiB accumulation in the posterior cingulate gyrus and precuneus, as well as in the frontal and temporal neocortices.…”
Section: Unraveling the Relationship Between Ad And Cardiovascular Rimentioning
confidence: 99%
“…Research such as this has produced new diagnostic options for clinical use. For example, in 2012, the Food and Drug Administration (FDA) approved an imaging technique that uses positron emission tomography (PET) scanning with the radioactive tracing compound florbetapir F-18 to identify the accumulation of amyloid-β plaques, which are believed to play a central role in AD [9]. The clinical implications of these advances are being actively discussed [3,4,10,11].…”
Section: Introductionmentioning
confidence: 99%